Prediabetes Education: the Underutilized Tool of Diabetes Prevention among Indian Population - Konikuzhiyil, Mohsina Hyder; Balasubramaniam, Vishwanathan; Undela, Krishna; Ponnusankar, Sivasankaran (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: This review aims to discuss the major effective educational interventions carried out among prediabetes population in different countries during the year 2001 to 2020. Materials and Methods: A PubMed, Science direct and Google Scholar detailed search was done on prediabetes education interventions and the search was limited to full text English articles with exclusions on articles with insufficient details. Youth diabetes prevention clinic for prediabetes, prediabetes booklet, web based meme generator, environmental posters, self assessment questionnaire, development of mobile health application, Smart watch activity trackers and home based counseling was found to be newer effective successful strategies ongoing in developed countries. Results: Detailed search and analysis could reveal that prediabetes educational interventions brought positive outcomes on improvements in fasting blood sugar, random blood sugar, fasting lipid profile and anthropometric parameters along with better life style changes. Conclusion: Education accompanied with self management training plays a crucial role in the management of early stages of diabetes. This review made an effort to highlight the effectiveness of each type interventions in prediabetes management in areas like nutrition, physical activity, weight management and stress relaxation which can be merged effectively in a better modified version and can be utilized in the future prevention trials in india.
Keywords: Educational Intervention; India; Lifestyle modification; Prediabetes; Empowerment; Prediabetes Counseling; Health promotion